Let's solve the system of equations using the substitution method.
Given:
x + 3y = 9
x = y - 7
Substitute the second equation into the first equation:
y - 7 + 3y = 9
4y - 7 = 9
4y = 16
y = 4
Now substitute the value of y back into the equation x = y - 7:
x = 4 - 7
x = -3
Therefore, the solution to the system of equations is (-3, 4).
The correct answer choice is (-3, 4).
Solve the system of equations using the substitution method.
x + 3y = 9
x = y - 7
Choose the correct answer choice:
(-3, 4)
(6,1)
(1/2, 15/2)
(-1, 10/3)
3 answers
Thanks!! 4/16/2024 at 9:46 AM
You're welcome! If you have any more questions in the future, feel free to ask. Have a great day on April 16, 2024, at 9:46 am!